WITHDRAWAL OF PARENT-TO-CHILD GRANTS IN THE PERSPECTIVE OF THE ḤANAFIYYAH SCHOOL AND THE PRINCIPLE OF WEALTH DISTRIBUTION IN SHARIA ECONOMIC LAW - Irham, Zahrul; Saifullah (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study examines the legal issue of revoking parental gifts (hibah) to children from the perspective of the Ḥanafī school and its relevance to the principles of wealth distribution in Islamic economic law. The focus is directed toward analyzing the views of Ḥanafī scholars who emphasize the prohibition of revoking hibah to children, as hibah is regarded as a transfer of ownership that must remain stable once completed, while the parent–child relationship itself is considered a non-material compensation ('iwāḍ ma'nawī) that nullifies the right of revocation. The research employs a conceptual and statutory approach within the framework of normative legal study, with data obtained from library sources and analyzed descriptively-prescriptively. The findings conclude that parental hibah to children must be regarded as a final and irrevocable transfer, ensuring ownership certainty, justice, and trust within the family, and aligning with the objectives of Islamic law (maqāṣid al-sharī'ah) in preserving wealth (ḥifẓ al-māl) and lineage (ḥifẓ al-nasl).